2015
DOI: 10.1016/j.ijrobp.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms for Prediction of Outcome With or Without Adjuvant Radiation Therapy for Patients With Endometrial Cancer: A Pooled Analysis of PORTEC-1 and PORTEC-2 Trials

Abstract: The nomograms are internally validated and able to accurately predict long-term outcome for endometrial cancer patients with observation, pelvic EBRT, or VBT after surgery. These models facilitate decision support in daily clinical practice and can be used for patient counseling and shared decision making, selecting patients who benefit most from adjuvant treatment, and generating new hypotheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 26 publications
1
42
1
3
Order By: Relevance
“…The question that remains is whether or not an additional BT boost is required. It seems that the incidence of vaginal recurrence after pelvic RT is low being between 1.6 and 2.3 % for early stage intermediate or high risk disease [ 46 , 49 ]. There are currently no randomized trials comparing EBRT vs EBRT with BT.…”
Section: Discussionmentioning
confidence: 99%
“…The question that remains is whether or not an additional BT boost is required. It seems that the incidence of vaginal recurrence after pelvic RT is low being between 1.6 and 2.3 % for early stage intermediate or high risk disease [ 46 , 49 ]. There are currently no randomized trials comparing EBRT vs EBRT with BT.…”
Section: Discussionmentioning
confidence: 99%
“…The PORTEC-1 criteria do not incorporate lymphovascular invasion, which has been identified as an independent prognostic factor in numerous studies. [21][22][23][24] Bendifallah et al found that incorporation of lymphovascular invasion significantly improved prognostic accuracy; this was later validated by Korkmaz et al 25 26 Our criteria also include higher-risk grade 2 patients who are omitted by the PORTEC-1 criteria. In comparison with the GOG-99 criteria, our proposed criteria facilitate ease of use and practical application owing to more straightforward age groupings and use of modern FIGO staging.…”
Section: Discussionmentioning
confidence: 75%
“…A recently published pooled data from the PORTEC-1 and PORTEC-2 trials incorporate these prospective data, which better elucidate outcomes with and without adjuvant therapy and validate these findings with large retrospective datasets [12]. The final nomogram identified age, FIGO grade, and LVSI as clear prognostic factors in all outcomes.…”
Section: Resultsmentioning
confidence: 86%